The crisis of the hero The cinematographic representation of the underground (Itinera, 2023)
The following article analyzes the parallelism between Notes from Underground by Fëdor Dostoevsky and Martin Scorsese’s Taxi Driver. The link between these works was made explicit by the director in a documentary movie about his career. The article revolves, therefore, around the underground as a place of intimate alienation and painful incommunicability. As a key to the interpretation, I used the studies of René Girard. In his essay about Dostoevsky he shows the underground as the place of the perversion of desire. The triangular structure subject-mediator-object becomes the source of deep obsession and rivalry: the mediator is for the subject who imitates him worshipped model and hated rival at the same time. In conclusion of the article, I will investigate the resolution hypothesis of Dostoevsky and Girard. Those hypotheses will then be compared with Travis’ story to try to understand if the man who has been harmed by the crisis of desire can come out as a winner from the underground.
Keywords: Underground, Girard, Mimetic desire, Trauma.